জীবনানন্দ সমীক্ষণ - মনিরুজ্জামান, মোহাম্মদ (ঢাকা : পরমা, 2000)
Contributed articles on the works of Jibanananda Das, 1899-1954, Bengali poet.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Das, Jibanananda, -- 1899-1954 -- Criticism and interpretation